Expression Profile of Genes Potentially Associated with Adequate Glycemic Control in Patients with Type 2 Diabetes Mellitus - Sâmia Cruz Tfaile Corbi; Alliny Souza Bastos; Rafael Nepomuceno; Thamiris Cirelli; Raquel Alves dos Santos; Catarina Satie Takahashi; Cristiane S. Rocha; Silvana Regina Perez Orrico; Claudia V. Maurer-Morelli; Raquel Mantuaneli Scarel-Caminaga (Journal of Diabetes Research)
Despite increasing research in type 2 diabetes mellitus (T2D), there are few studies showing the impact of the poor glycemic control on biological processes occurring in T2D. In order to identify potential genes related to poorly/well-controlled patients with T2D, our strategy of investigation included a primary screen by microarray (Human Genome U133) in a small group of individuals followed by an independent validation in a greater group using RT-qPCR. Ninety patients were divided as follows: poorly controlled T2D (G1), well-controlled T2D (G2), and normoglycemic individuals (G3). After using affy package in R, differentially expressed genes (DEGs) were prospected as candidate genes potentially relevant for the glycemic control in T2D patients. After validation by RT-qPCR, the obtained DEGs were as follows—G1 + G2 versus G3: HLA-DQA1, SOS1, and BRCA2; G2 versus G1: ENO2, VAMP2, CCND3, CEBPD, LGALS12, AGBL5, MAP2K5, and PPAP2B; G2 versus G3: HLA-DQB1, MCM4, and SEC13; and G1 versus G3: PPIC. This demonstrated a systemic exacerbation of the gene expression related to immune response in T2D patients. Moreover, genes related to lipid metabolisms and DNA replication/repair were influenced by the glycemic control. In conclusion, this study pointed out candidate genes potentially associated with adequate glycemic control in T2D patients, contributing to the knowledge of how the glycemic control could systemically influence gene expression.